Blood Lipid Profile of Broiler Chickens Fed a Step Down Protein With Addition of Lime Juice as an Acidifier - S. Hasanuddin; V. D. Yunianto; . Tristiarti (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
The aim of this research was to evaluate the effect of lime juice (LJ) and citric acid (CA) as an acidifier in the step down protein feeding system on the blood lipid profiles. The research was conducted with 192 of 7 days old broiler chickens which were arranged in a completely randomized design with 6 treatments and 4 replications, so overall there were 24 experimental units. Each experimental unit consisted of 8 broiler chickens. Treatments applied were P0 (control diet, without step down), P1 (step down diet), P2 (step down diet + CA 0.8%), P3 (step-down + LJ equivalent to 0,4% CA (6,9 ml/100g feed)), P4 (step down diet + LJ equivalent to 0,8% CA (13,8 ml/100g feed)) and P5 (step down diet + LJ equivalent to 1,2% CA (20,7 ml/100g feed)). The parameters measured in this research were cholesterol, triglycerides, low density lipoprotein (LDL) and high density lipoprotein (HDL) in the blood serum. The results showed that the step-down protein feeding with the addition of acidifier such as synthetic citric acid or lime juice was not significant (P> 0.05) in lowering blood cholesterol levels, triglycerides and LDL and did not result in an increase of serum HDL levels in broiler chickens.